Nitric Oxide, an Essential Intermediate in the Plant–Herbivore Interaction - Arnaiz, Ana; Rosa-Diaz, Irene; Romero-Puertas, Maria C.; Sandalio, Luisa M.; Diaz, Isabel (Frontiers in Plant Science, 2021)
Reactive nitrogen species (NRS), mainly nitric oxide NO, are highly reactive molecules with a prominent role in plant response to numerous stresses including herbivores, although the information is still very limited. This Perspective article compiles the current progress in determining the NO function, either as signal molecule, a metabolic intermediate, or a toxic oxidative product, as well as the contribution of molecules associated to NO-metabolic pathway in the generation of plant defences against phytophagous arthropods, in particular to insects and acari.